chemistry students perception toward english technical vocabulary in their discipline - fitriyani, novita; wahyunengsih; hafeeza, aqsha (Journal of Research and Education Chemistry, 2026)
English technical vocabulary is an important component in chemistry learning, particularly for understanding concepts, laboratory activities, and scientific references. This study aims to examine chemistry students’ perceptions of English technical vocabulary in terms of its importance, challenges, learning strategies, and instructional needs. A descriptive quantitative approach was employed using a Likert-scale questionnaire administered to 57 undergraduate chemistry students at UIN Syarif Hidayatullah Jakarta who had completed chemistry courses involving English terminology. The results indicate that students have a high perception of the importance of English technical vocabulary (M = 4.06), especially in supporting academic activities such as reading textbooks and understanding scientific articles. However, students also experience moderate challenges in mastering technical vocabulary (M = 3.82), particularly in distinguishing terms with similar meanings. To address these difficulties, students actively employ various learning strategies (M = 3.90), mainly through contextual learning, routine reading, peer discussion, and the use of digital tools. In addition, students express a strong need for systematic instructional support (M = 3.98), including collaboration between chemistry and English lecturers. Overall, the findings suggest that although English technical vocabulary is perceived as essential, targeted and integrated vocabulary instruction within chemistry courses is still required to reduce learning difficulties and support students’ conceptual understanding.